Optimising sealed transports of small ornamental fish - Silva, Rui E. (2022)
This paper reports on simulated long-term transports of small ornamental fish inside sealed containers. The species involved were Diplodus sargus, Gobius paganellus, Gobiusculus flavescens, Lepadogaster lepadogaster, and Lipophrys pholis. The objective of such simulations was to determine the maximum bioload that it is possible to move inside a sealed container, while ensuring 100% survivorship, ultimately resulting in financial savings for the end-receiver. Transports were simulated over 24, 48 and 72 hours, with increasing animal bioloads per bag. Fifty percent of the trials were performed with “regular” saltwater while the other half involved seawater buffered with Amquel®, sodium carbonate and sodium bicarbonate, with the objective of keeping ammonia low and pH similar to initial baseline values. At the end of each trial, temperature, dissolved oxygen, pH and ammonia were analysed and survival rates determined. L. lepadogaster endured the highest bioloads and displayed 100% survivorship (i.e. up to 30 g/L), which is not surprising given the intertidal nature of this species. D. sargus exhibited mortalities with bioloads as low as 3.23 g/L, which echoes its predominantly pelagic nature and relatively lesser ability to endure confinement. The three remaining species showed varying degrees of tolerance to increasing bioloads in transport: L. pholis, also an intertidal species, tolerated up to 20 g/L over 72 hours, while G. paganellus tolerated up to 7 g/L over 72 hours, and G. flavescens (a predominantly pelagic species) could tolerate no more than 6 g/L up to 72 hours.